DEVELOPMENT OF A FOUNDATIONAL PLAY-BASED INTERVENTION MODEL THROUGH PARENT AND PAUD TEACHER COLLABORATION TO ENHANCE SOCIAL SKILLS IN AUTISTIC CHILDREN - Esty Faatinisa; Endang Rochyadi; Achmad Hufad; Imas Diana Aprilia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Play is widely recognized as an effective method for enhancing social skills in autistic children. However, play involves developmental stages that necessitate alignment with the child's specific play abilities. Consequently, there is a need for a play-based intervention model that can be utilized by parents and early childhood education teachers to improve social skills in autistic children within Early Childhood Education (PAUD) settings. This study aimed to develop an effective play-based model for enhancing social skills in autistic children by maximizing the roles of both parents and teachers. This research employed a mixed-methods approach using an Exploratory Sequential Design. Research data were obtained from two playgroup (Kober) teachers, three mothers of autistic children attending these playgroups, and three autistic children who served as the primary intervention subjects. Data collection techniques included observation, interviews, and documentation. Qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. Meanwhile, quantitative data were analyzed using the Single Subject Research (SSR) method, focusing on within-condition and between-condition analyses, as well as calculating the average skill improvement of the subjects. The research findings indicate that: (1) The social skills of autistic children were notably low, particularly in eye contact ability and imitation behavior, which are fundamental social skills for autistic children. (2) The play patterns implemented by teachers and parents thus far tended not to consider the child's developmental stage and play abilities. (3) The model's development was based on empirical studies (needs analysis) and a comprehensive literature review that informed the concept and implementation process of the foundational play-based intervention model for parent-teacher collaboration. (4) Based on the evaluation, the foundational play-based intervention model involving parent-teacher collaboration was found to be effective in enhancing the social skills of autistic children, specifically in their eye contact ability and imitation behavior.